2022
DOI: 10.58807/indexenferm20225402
|View full text |Cite
|
Sign up to set email alerts
|

Versión en español de la escala Maternal Breastfeeding Evaluation Scale: Análisis de fiabilidad y validez

Abstract: Fundamento: Es necesario el desarrollo de herramientas válidas que midan la satisfacción en la lactancia materna para analizar los comportamientos de lactancia materna y evaluar la efectividad de las intervenciones. El cuestionario Maternal Breastfeeding Evaluation Scale (MBFES) es uno de los más utilizados, pero carece de versión en español. El objetivo de este trabajo es traducir el cuestionario al español y evaluar sus propiedades psicométricas. Métodos: Para su traducción se utilizó el método de traducción… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Consequently, we opted to use the original structure in the present study. The results also suggest good internal consistency of the dimensions, consistent with various versions [15,17,19].…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Consequently, we opted to use the original structure in the present study. The results also suggest good internal consistency of the dimensions, consistent with various versions [15,17,19].…”
Section: Discussionsupporting
confidence: 75%
“…The MBFES has been validated in various languages and contexts, demonstrating good psychometric properties across its different versions. Con rmatory factor analysis showed that the data t the original structure [15] and the proposed structure for the validated Spanish version [19]. Both versions, following exploratory factor analysis [15,19] resulted in a scale comprising 30 items and three interrelated dimensions.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations